2017
DOI: 10.3390/ijms18122734
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Structural Requirements of Potent Brassinosteroids as Vegetable Growth Promoters Using Second-Internode Elongation as Biological Activity: CoMFA and CoMSIA Studies

Abstract: In the present study, we have employed the ligand-based drug design technique, 3D-QSAR, through a comparative molecular field analysis (CoMFA) and a comparative molecular similarity indices analysis (CoMSIA) to determine the key factors for the plant growth promoting activity of brassinosteroids reported in literature, using the bean second-internode bioassay measured on two groups of compounds with different molar concentrations. This is the first 3D-QSAR study using the second internode elongation as biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Additionally, BRs analogues obtained from deoxycholic and hyodeoxycholic acids have turned out to show excellent bioactivity in the rice lamina inclination assay [ 72 , 73 ]. Using a 3D-QSAR it has been possible to establish a structure-activity relationship which indicates that activity is favored by the following structural parameters: presence of hydroxyl groups at C22 and voluminous group in the end of alkyl chain; the hydroxyl group in C3 of ring A is indispensable [ 74 ]. The 3D contour maps showed that the growth promoting activity of the compounds was influenced mainly by electrostatic properties and the presence of hydrogen-bond acceptor groups [ 74 ].…”
Section: Design and Synthesis Of Molecules For The Exogenous Stimumentioning
confidence: 99%
“…Additionally, BRs analogues obtained from deoxycholic and hyodeoxycholic acids have turned out to show excellent bioactivity in the rice lamina inclination assay [ 72 , 73 ]. Using a 3D-QSAR it has been possible to establish a structure-activity relationship which indicates that activity is favored by the following structural parameters: presence of hydroxyl groups at C22 and voluminous group in the end of alkyl chain; the hydroxyl group in C3 of ring A is indispensable [ 74 ]. The 3D contour maps showed that the growth promoting activity of the compounds was influenced mainly by electrostatic properties and the presence of hydrogen-bond acceptor groups [ 74 ].…”
Section: Design and Synthesis Of Molecules For The Exogenous Stimumentioning
confidence: 99%
“…In this way, BRs analogs with shorter side chains [19][20][21][22] and/or including a variety of substituents [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] have been reported. The biological activity of these synthetic BRs analogs seems to depend on the spatial distribution of oxygen atoms instead of the presence or absence of one specific functional group in the molecule [11,18], and consequently some new SAR have been proposed [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Partial least squares (PLS) is an extension of the multiple regression (MR). It was applied to linearly correlate the variance in CoMSIA and CoMFA fields to variations in pIC 50 values of compounds [ 40 ]. In this study, PLS was performed in two stages including the first with leave-one-out (LOO) cross-validation to obtain the optimal number of components (ONC), which represents the complexity level of a model and corresponds to the highest cross-validated r 2 (called q 2 ) [ 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%